Simulation on The Effect of Fluid Velocity on The Flow and Structure Performance of The Pipeline in UTHM Biodiesel Pilot Plant - Abdul Rashid, Norfatihah; Mohd Salleh, Zuliazura; Hussin, Rosniza; Abd Rashid, Razlin (Progress in Engineering Application and Technology, 2020)
Fuels are produced from biological feedstock known as biofuels. Nowadays, biodiesel has been reported to be one of the strong contenders for reductions in exhaust emission because of its more environment friendly and renewable fuels. In biodiesel plant, piping is the most important part because it is the main transport system used to transfer the biodiesel oil from one process to another. The purpose of this study is to investigate the flow behaviour and structure performance effect to the piping line by using three different velocities inlet (0.01 m/s, 0.02 m/s and 0.03m/s). The outcome from this study is to know which part have the highest possibilities in risk.. The main geometry of the piping line was based on UTHM Biodiesel Pilot Plant. This study focused on piping line from esterification process until trans-esterification  process. Simulation were conducted to determine the velocity distribution, pressure and stress along the. The simulation were done by using ANSYS software. From the simulation, the highest risk occurred at velocity inlet  0.03 m/s with the maximum stress located at fitting 8 with maximum stress recorded at 2.878e8 Pa.